2021
DOI: 10.1016/j.ejca.2021.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment for melanoma in clinical practice – Trial versus reality

Abstract: Background: Little is known about outcomes of adjuvant-treated melanoma patients beyond the clinical trial setting. Since 2019, adjuvant-treated melanoma patients have been registered in the DMTR, a population-based registry to monitor the quality and safety of melanoma care in the Netherlands. This study aims to describe treatment patterns, relapse, and toxicity rates of adjuvant-treated melanoma patients beyond the clinical trial setting. Methods: Analyses were performed on adjuvant-treated melanoma patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 15 publications
2
28
1
Order By: Relevance
“…However, both for dabrafenib plus trametinib and nivolumab, the relative number of patients who ended treatment due to toxicity was higher than in the trials. This was also observed in the studies of de Meza et al and Hoffmann et al, which showed higher treatment-limiting AEs on ICI in clinical practice [ 21 , 22 ]. As far as we know, no other real-world data have been published with treatment-limiting toxicity rates for dabrafenib plus trametinib.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…However, both for dabrafenib plus trametinib and nivolumab, the relative number of patients who ended treatment due to toxicity was higher than in the trials. This was also observed in the studies of de Meza et al and Hoffmann et al, which showed higher treatment-limiting AEs on ICI in clinical practice [ 21 , 22 ]. As far as we know, no other real-world data have been published with treatment-limiting toxicity rates for dabrafenib plus trametinib.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, we reported severe hepatitis ( n = 2), asthenia ( n = 1), and diarrhea ( n = 1) during treatment with nivolumab and diarrhea ( n = 2), and colitis ( n = 1) during pembrolizumab. De Meza et al did report higher rates of severe AEs in clinical practice compared to the RCTs [ 21 ]. Due to the low incidence of the individual severe AEs, we could not determine if this was the case for our study population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy of this study was 65 percent to decision tree algorithms and CNN classifiers [15] [16]. Some essential pre-trained neural networks have struggled to learn a single class with excellent accuracy [8][17] [18]. The paper [16] has taken 200 melanoma and 300 standard samples.…”
Section: Discussionmentioning
confidence: 99%